Pengembangan Problem and Project Based Learning Pasca Covid-19 terhadap Kolaborasi Peserta Didik - Buda, Chinda Hibatul; Wardani, Naniek Sulistya; Prasetyo, Aris Kukuh (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to determine whether the improvement of students' collaboration skills in thematic learning can be pursued through Problem and Project Based Learning (PPjBL) and how the improvement of students' collaboration skills in thematic learning can be pursued through Problem and Project Based Learning (PPjBL). The subject of this research is 4th-grade elementary school students in the even semester of the 2021/2022 academic year with a total of 8 students. This type of research is classroom action research (CAR). The CAR model from Stringer ET with the steps of look, think, act. The research procedure is carried out in two cycles. The data collection technique used observation. The research instrument was in the form of an observation sheet. The data analysis technique was a comparative descriptive technique. The results of the study stated that there was an increase in the collaboration skills of fourth-grade students in thematic learning through PPjBL proven. The increase in the number of students is yes. skilled in collaboration. The increase in average collaboration between students in cycles I and II increased by 4.93%. The average collaboration between students in the first cycle was initially at 77.75%, then increased to 82.68% in the second cycle. Improving the collaboration skills of fourth graders in thematic learning through PPjBL with the following steps: 1) identifying problems, 2) finding problems, 3) forming groups, 4) designing projects, 5) conducting research, 6) collecting data/information together groups, 7) prepare reports and publications, and 8) reflection on the problem-solving process.